The impact of haze on the adolescent's acute respiratory disease: A single institution study - Wan Yaacob, Wan Fairos; Mohamad Noor, Nor Suhana; Che A. Bakar, Nor Ili; Mat Zin, Nurulhuda Afisah; Taib, Fahisham (Elsevier, 2016)
Objective: To examine the impact of haze in the reduction of peak expiratory flow rate (PEFR) reading and identify the risk factors affecting respiratory function due to haze. Methods: This study was conducted during haze period among secondary school students in Kota Bharu. We analyzed data on a total of 126 secondary school children measuring the respiratory health and symptoms in October 2015 using standardized questionnaire and PEFR measurement. Clinical characteristics on the risk factor and prevalence of haze effect were explored. Chi-square test and independent sample t-test was used to investigate the relationship between risk factors and haze effect and logistic regression analysis for the odds of having haze effect. Results: The findings revealed a significant reduction in PEFR reading of more than 15% from the expected PEFR values. It was also noted that the children with headache, cough, mucus and sore throat respiratory symptoms had consistently higher rates of respiratory illness of having haze effect compared to those who did not. Conclusions: Student with haze effect documented much higher symptoms during haze especially female students. Symptoms such as headache, wheezing and mucus were noted among the normal secondary school children in Kota Bharu.